2011
DOI: 10.3389/fpsyg.2011.00372
|View full text |Cite
|
Sign up to set email alerts
|

Unimanual SNARC Effect: Hand Matters

Abstract: A structural representation of the hand embedding information about the identity and relative position of fingers is necessary to counting routines. It may also support associations between numbers and allocentric spatial codes that predictably interact with other known numerical spatial representations, such as the mental number line (MNL). In this study, 48 Western participants whose typical counting routine proceeded from thumb-to-little on both hands performed magnitude and parity binary judgments. Respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 59 publications
7
54
3
Order By: Relevance
“…A mental simulation account would be consistent with past research by Domahs et al (2012) which indicated that the complexity of finger number gestures may modulate the degree to which counting habits appear to influence cognition. This would also be consistent with a growing literature which suggests that finger-counting direction, as well as hand orientation may impact performance when matching number parity or magnitude with left/right space (Conson, Mazzarella, & Trojano, 2009;Iversen et al, 2006;Michaux, Masson, Pesenti, & Andres, 2013;Riello & Rusconi, 2011).…”
Section: Finger-counting Simulationsupporting
confidence: 90%
See 1 more Smart Citation
“…A mental simulation account would be consistent with past research by Domahs et al (2012) which indicated that the complexity of finger number gestures may modulate the degree to which counting habits appear to influence cognition. This would also be consistent with a growing literature which suggests that finger-counting direction, as well as hand orientation may impact performance when matching number parity or magnitude with left/right space (Conson, Mazzarella, & Trojano, 2009;Iversen et al, 2006;Michaux, Masson, Pesenti, & Andres, 2013;Riello & Rusconi, 2011).…”
Section: Finger-counting Simulationsupporting
confidence: 90%
“…Additionally, given the low baseline error-rate in this task, and over-representation of participants whom made no errors in certain comparisons, there was a significant positive skew in the data. Although other studies using these types of data have used a simple arcsine transformation for error proportions (Domahs et al, 2010;Riello & Rusconi, 2011), these transformations actually increase positive skew in error proportions that are close to floor, rendering subsequent analyses excessively liberal. Therefore, all mean error-rate data was normalized using an arcsine square root transformation y = asin(sqrt(x)) prior to data analysis, which better reduced skew and rendered subsequent analyses more conservative.…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence that spatial location influences descriptive associations. For example, small numbers are associated with the left position and large numbers with the right position—an effect known as spatial‐numerical association of response codes, SNARC (Dehaene, Bossini, & Giraux, ; Riello & Rusconi, ). In the domain of abstract concepts, a well‐known example is the association of the future and the past with forward or backward motion (Boroditsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed that a fingerbased reference frame could interact with the SNARC effect. In a parity task where subjects were asked to respond with the index and middle fingers of either their right or their left hand, Riello and Rusconi (2011) observed that unimanual SNARC effects were modulated by participants' hands position. When participants' hands were placed palm down, a unimanual SNARC effect was observed with the right hand, whereas a unimanual SNARC effect with the left hand was observed when the hands were palm up.…”
Section: Finger-based Reference Framesmentioning
confidence: 99%